Talent Management for Empirical Enlargement - Ratika Agarwal (International Journal of Engineering and Management Research, 2019)
In a Dynamic environment, human resources are one of the important sources of the organizational Enlargement which also helps to take fighting edge. Human resource system contributes towards the empirical enlargement through facilitating the change & by developing the competencies of the employees. Talent Management is the key for improved business performance & for the empirical enlargement of an organization. The linkage between talent management and Empirical Enlargement will help to attain higher organizational performance. Many studies have been conducted regarding how companies can gain a empirical fierce edge through their human resources & proper knack management. Having talented employees helps the firms drive and boost for organizational success. knack management is of strategic importance & by developing the talent, organizations may develop strong leadership teams which will help to take fierce edge and that will enable the organization to achieve its goals & organizational success.